Labor Market And Professional Integration Of Youth In Lebanon: Why Employment Fails? - Nehme, Eliane; Nehme, Georges (European Scientific Journal, ESJ, 2016)
The labor market is not like any other market. It has been the subject of a sufficiently developed theoretical analysis such as the neoclassical model and other complementary or opposed alternative theories. The rigidity of the labor market and the gap between labor supply and labor demand, is due to multiple factors. Companies’ limitations are mostly due to their structure, their economic activity, the labor costs, and the absence of structural macroeconomic policies. Moreover, restrictive monetary policy creates pressure on the labor market and increases unemployment. The objective of this research is to prepare, a structural study on labor market and emigration in Lebanon in order to highlight the problems of youth professional integration, the factors of recruitment, the conditions of work, the nature of the activity, and the factors and reasons of emigration. It also aims to propose policies and guidance to overcome the above mentioned difficulties so as to ensure good jobs for young people and prevent emigration.